2016
DOI: 10.1371/journal.pone.0159578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Circadian Rhythm Sleep-Wake Disorders and Associated Factors in Euthymic Patients with Bipolar Disorder

Abstract: Recent studies have suggested that there are certain pathophysiological relationships between bipolar disorder (BD) and circadian rhythm dysfunction. However, apparently no studies have clarified the prevalence of circadian rhythm sleep-wake disorders (CRSWD) in patients with BD. This study was set out to investigate the prevalence of CRSWD and associated factors in patients with BD. One hundred four euthymic BD outpatients participated in this study. The subjects were asked to answer questionnaires including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 51 publications
1
24
1
Order By: Relevance
“…The aim of this review was to summarize and discuss the recent researches on the relations between circadian rhythm dysfunction and BD (listed in Table ). Moreover, I discuss the clinical implication of circadian rhythm dysfunction on the clinical diagnosis and treatment of BD.…”
Section: Summary Of the Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this review was to summarize and discuss the recent researches on the relations between circadian rhythm dysfunction and BD (listed in Table ). Moreover, I discuss the clinical implication of circadian rhythm dysfunction on the clinical diagnosis and treatment of BD.…”
Section: Summary Of the Study Findingsmentioning
confidence: 99%
“…Sleep disturbances have also been reported to be frequent in the euthymic state . Past studies have demonstrated that the sleep disturbances in the euthymic state included not only insomnia but also sleep–wake rhythm disorders, especially delayed sleep–wake phase disorders, suggesting that circadian rhythm dysfunction could be involved in the pathophysiology of BD. Pinho et al .…”
Section: Circadian Rhythm Markers In Bdmentioning
confidence: 99%
“…Clinical symptoms that are frequently reported include sleep timing disturbances , irregular daily schedules , and an evening preference . These symptoms of circadian disruption may occur during episodes, while euthymic , and in those at high risk for bipolar disorder . Even small changes to circadian rhythms such as the shift to daylight savings time may have adverse mental health consequences .…”
Section: Introductionmentioning
confidence: 99%
“…The connection between the CR disruption and bipolar disorder (BD) also has been well documented in the past and current research. Takaesu et al (2016) explained the dysfunction of CR due to sleep disturbance among euthymic bipolar disorder (BD) patients. Participants went through a clinical interview and had a sleep log for researchers to monitor participants' sleeping pattern before they were categorised for sleep disorder according to International Classification of Sleep Disorders-3rd Edition…”
Section: Circardian Rhythm and Bipolar Disordermentioning
confidence: 99%